2003
DOI: 10.1002/bdrb.10005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the nonsteroidal anti‐inflammatory drug literature for potential developmental toxicity in rats and rabbits

Abstract: This analysis of the non-clinical NSAID literature demonstrated a possible association between exposure to NSAIDs and developmental anomalies. The anomalies were similar for aspirin and for other NSAIDs, but effects occurred at a much lower incidence with non-aspirin NSAIDs than previously reported with aspirin. Such a finding is consistent with the concept that reversible inhibition of COX-1 and/or COX-2 by other NSAIDs would produce weaker developmental toxicity signals than aspirin. However, there were limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 81 publications
4
56
0
3
Order By: Relevance
“…Cook et al [20] presented similar findings. However, these were restricted to non-selective COX inhibitors.…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 61%
See 1 more Smart Citation
“…Cook et al [20] presented similar findings. However, these were restricted to non-selective COX inhibitors.…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 61%
“…Nevertheless, the role of disorders in the function and morphology of the placenta in their etiopathogenesis remains unknown. Briggs et al [20] indicate that xenobiotics can easily cross the placental barrier which separates the mother's circulatory system from the foetal circulation.…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%
“…In the contemporary study, the medicine was administered systemically to evaluate the effect on the dental tissues of the neonates. Review of the literature indicated the potential association of NSAIDs with developmental toxicity of diaphragmatic hernia, midline defect and ventricular septal defects in rats and rabbits Gupta et al, 2003;Cook et al, 2003). The rate of perinatal mortality was reported providing the information of high-risk pregnancies, where aspirin treatment seemed to have a small but significant effect on reducing the rate of preterm deliveries, but did not reduce the rate of perinatal death (Kozer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Позднее были опубликованы свидетельства возрастающего риска орофациальных расщелин и ВПС, в частности аномалий развития сердечной перегородки [78][79][80]. Ацетилсалициловая кислота (Аспирин) является единственным НПВП, который необратимо ингибирует ЦОГ путем ацетилирования, с чем, по-видимому, связана более высокая распространенность ВПР в исследова-ниях на животных [81]. В настоящее время связь между полиморфизмом материнских ферментов ЦОГ-1 и ЦОГ-2 и возросшей частотой врожденных аномалий остается неизученной.…”
Section: обзор литературыunclassified